Gross Adaptive Morphologic Changes Occurring in the Gastrointestinal Tract Components of Ostriches Fed Ration Including or Excluding Grit in Botswana - Waugh, E.E.; Dzoma, B.M.; Seabo, D.; Aganga, A.A.; Tsopito, C.M.; Omphile, U.J.; Sebolai, B.; Malela, L. (International Journal of Poultry Science, 2007)
This study investigated the gross changes occurring in the luminal surface and structural anatomy of some Gastrointestinal Tract (GIT) components of ostriches with access to grit and of ostriches without access to grit. Fourteen ostrich chicks age ten weeks were raised on concrete without access to grit were randomly assigned to two feeding groups. Each feeding group had seven birds raised in a pen 30 meters long by 6 meters wide. All ostriches were fed and watered ad libitum. One group had access to grit through out the study while the other group did not have access to grits. From week 24 an ostrich from each group was slaughtered monthly. Gastrointestinal components were dissected and weights with and without contents recorded. The length of tubular components was measured. Digital photographs were taken of the external morphology and of the luminal surfaces of proventriculus and ventriculus (gizzard). Measurements were taken of the height of proventricular mucosal folds and the thickness of the ventricular muscle. The volume of the proventriculus and of the ventriculus was determined by measuring the volume of water displaced by the organs. The data was analyzed using the student-t test at p